Hábitos e interesses dos usuários da Biblioteca Central da Universidade Federal de Pernambuco - Melo, Louicira Goldstein Costa (1978)
Students and universitary teachers are analysed as library users and their habitudes and interests demonstrated during the process of information gathering are studied through the application of a questionnaire. Various groups os students and professors belonging to different university centers are observed.